The compassionate classroom : relationship-based teaching and learning - Hart, Sura (PuddleDancer Press, 2004)
This is a long awaited how-to guide for educators who care about creating a safe, productive learning environment. With 45 years combined teaching experience, Sura Hart and Victoria Kindle Hodson merge recent discoveries in brain research with the proven skills of Non-violent Communication and come to a bold conclusion - when compassion thrives, so does learning. Learn powerful skills to create an emotionally safe learning environment where academic excellence thrives. Build trust, reduce conflict, improve co-operation, and maximise the potential of each student as you create relationship-cent.